The Relationship of Stress Level to Blood Sugar Levels in Diabetic Mellitus Patients at UPTD Puskesmas Terara - Hamdiana, Lili; Wahyudi, Iwan; Pa'ni, Daeng Mustamu Qamal; Amrullah, Muhammad (THRIVE Health Science Journal, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by elevated blood sugar levels due to insulin deficiency or resistance. Stress is a significant factor that can exacerbate blood glucose dysregulation by increasing cortisol levels, which reduces insulin sensitivity. This study investigates the relationship between stress levels and blood sugar levels in DM patients at UPTD Puskesmas Terara. A cross-sectional design was employed with 60 respondents, and data were collected using a stress level questionnaire and blood glucose laboratory tests. The Spearman Rank correlation analysis revealed a significant relationship between stress levels and blood sugar levels (p = 0.000, α = 0.05). The majority of respondents (58.3%) experienced severe stress, and 65.0% had high blood sugar levels. Findings suggest that increased stress levels correlate with poor glycemic control in DM patients. Addressing psychological stress through lifestyle modifications and stress management interventions may improve diabetes management outcomes. Future research should explore stress reduction strategies and their impact on long-term glycemic control